Biological hazards at the nurse's workplace - Tomaszewska, Katarzyna; Kisiel, Renata (Journal of Education, Health and Sport, 2023)
Occupational exposure to blood is a significant problem among health care workers. Nurses are a group that is particularly at risk. Exposure can lead to HBV, HCV or HIV infection. Extremely important for preventing exposures is improving knowledge of medical personnel about consequences of being infected by bloodborne pathogens, preventive measures and advantages of using those measures, and especially about post-exposure proceedings. The aim of the study was to assess the knowledge and opinions of nurses employed in anesthesiology and intensive care wards on occupational exposure and post-exposure management. Material and methods: A diagnostic survey method was employed for the research using author’s questionnaire. The study included 117 nurses working in the anesthesiology and intensive care units. Statistical analysis of the results was carried out using the descriptive statistics method. During the statistical verification p<0.05 was assumed as the level of significance of the obtained results. Results and conclusions: The level of knowledge and opinions of the surveyed nurses were not dependent on sociodemographic factors. Nurses use personal protective equipment and know post-exposure procedure, but don’t always follow it. Training doesn’t reduce the number of exposure cases. The most common mechanism of exposure is needle-stick injury.